Evaluation of a rehabilitation service for patients living with and beyond cancer: a randomised controlled trial. Issue 2 (1st June 2012) - Leurent, B.; Round, J.; Fitzgerald, G.; Davis, S.; Jones, L.
Abstract : Introduction: The Marie Curie Hospice in Hampstead provides a rehabilitative model of day care therapy to support patients living with and beyond cancer. This model was selected as a site of excellence for further attention in the National Cancer Survivorship Initiative 2008. We conducted a randomised controlled trial to evaluate the clinical and cost-effectiveness of this rehabilitation model. Aims and Methods: To test whether a rehabilitation service for patients living with cancer is clinically and cost-effective. A randomised controlled trial comparing a manualised rehabilitative intervention with a waiting-list control. Participants at the end of a course for treatment for recurrent hematologic or breast cancer were recruited between August 2010 and July 2011 from two London hospitals and followed-up for three months. Clinical outcomes included measures of supportive care needs, distress, continuity of care and quality of life. Cost-effectiveness analysis considered the incremental cost-effectiveness ratio for the intervention and control groups, with outcomes expressed as quality adjusted life years. Results: Recruitment was slower than expected, with a final number of 41 participants recruited to the trial against a target recruitment of 120. Referral rates were dependent on engagement of clinicians with concepts of hospice-based rehabilitation. Despite small numbers, we report evidence of effectiveness and cost-effectiveness. Conclusion: This trial used robust methodology to evaluate a complex intervention for patients living with cancer. Although fewer than expected were recruited, results should be indicative of the likelihood that the intervention is clinically and cost-effective, and highlight important methodological challenges faced by investigators working in this area.